Videojournalism : multimedia storytelling - Kobre, Kenneth, 1946- (Focal Press, 2012)
"The solo videojournalist must find a riveting story; gain access to charismatic characters who can tell their own tales; shoot candid clips; expertly interview the players; record clear, clean sound; write a script with pizzazz; and, finally, edit the material into a piece worthy of five minutes of a viewer's attention. Videojournalism addresses all of these challenges and more. ... Opening chapters cover the foundations of mutlimedia storytelling, and then the book progresses to the techniques required to shoot professional video, record high quality sound and market the resulting product"--Back cover.